Addressing the obstacles of CAR T cell migration in solid tumors: wishing a heavy traffic. (3rd October 2022) - Safarzadeh Kozani, Pooria; Safarzadeh Kozani, Pouya; Rahbarizadeh, Fatemeh
Abstract: Chimeric antigen receptor T cell (CAR-T) therapy has been recognized as one of the most prosperous treatment options against certain blood-based malignancies. However, the same clinical and commercial success have been out of range in the case of solid tumors. The main contributing factor in this regard is the hostile environment the tumor cells impose that results in the exhaustion of immune effector cells alongside the abrogation of their infiltration capacity. The discovery of the underlying mechanisms and the development of reliable counterstrategies to overcome the inaccessibility of CAR-Ts to their target cells might correlate with encouraging clinical outcomes in advanced solid tumors. Here, we highlight the successive physical and metabolic barriers that systemically administered CAR-Ts face on their journey toward their target cells. Moreover, we propose meticulously-devised countertactics and combination therapies that can be applied to maximize the therapeutic benefits of CAR-T therapies against solid tumors.